Development of JmjC-domain-containing histone demethylase (KDM2-7) inhibitors for cancer therapy. Issue 5 (May 2023) - Zhang, Lan; Chen, Yao; Li, Zhijia; Lin, Congcong; Zhang, Tongtong; Wang, Guan
Graphical abstract: Highlights: The dysregulation of JmjC-KDMs is closely related with various human diseases, especially cancers. The structures and transcriptional regulation of JmjC-KDMs are discussed. We describe the development strategies for the discovery of JmjC-KDM inhibitors. Specific inhibitors of JmjC-KDMs may act as promising agents in cancer therapy. Abstract : Histone methylation is the most common histone modification and a highly dynamic regulator of gene transcription. Methylation of lysine residues can alter the structure of chromatin, helping to regulate DNA-based nuclear activities. Lysine demethylases control and maintain epigenetic factors that affect chromatin structure and cell characteristics. A variety of diseases, including malignant tumors, are connected to their dysregulation. Advances in biochemistry and pathogenesis have prompted the discovery of small molecule inhibitors and tool compounds that disrupt lysine demethylation. In this review, we focus on JmjC-domain-containing histone lysine demethylases (KDM2–7), discussing their structures and biological roles, representative inhibitors, and therapeutic potential in cancer therapy, and aiming to provide unique insights into the development of JmjC-KDM inhibitors.